The physiology of zinc in the auditory system and its implications in tinnitus - Person, Osmar Clayton; Féres, Maria Cristina Lancia Cury (Medicina (Ribeirao Preto), 2005)
Zinc is an essential oligoelement in the human homeostasis and although it is present in small quantities in the body, it has an important role as metaloenzyme, acting throughout the metabolism. It is found in some neural circuitry acting as a modulator in glutamatergic systems. In the auditory system it is active in the cochlear nucleus and in the cochlea, where it acts in the antioxidant systems and the copper/zinc superoxide dismutase (Cu/ZnSOD) is considered the first- line defense against free radicals damage in the cochlea. According to some authors, it has the role of protecting the cochlea against damage caused by normal aging, noise, ischemia and ototoxic drugs. In the past few years, its physiology has been associated to tinnitus, a symptom that affects 17% of the general population and 33% of the elderly population and it is actually a problem for otorhinolaryngology. The present study reviews important aspects of the physiology of zinc in the auditory system and its relationship to tinnitus.